2003
DOI: 10.1021/nl034759v
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Photo Switching in Tethered Spiropyrans Using the Interfacial Force Microscope

Abstract: The interfacial force microscope has been used to establish the changes in the surface chemistry that accompany photoactivated opening and closing of rings in tethered spiropyran monolayers. Contact potential measurements show that ring opening via ultraviolet light creates a more polar surface, while exposure to visible light closes the rings and resets the surface. Normal force measurements show that open ring structures are protonated in electrolyte solutions, amplifying the switching of electrical double-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
58
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(59 citation statements)
references
References 10 publications
0
58
0
1
Order By: Relevance
“…Dieses System wurde verwendet, um durch die Absorption von UV-Licht reversible ¾nderungen der Benetzbarkeit durch das Schalten zu einem polareren, zwitterionischen Merocyanin-Isomer zu bewirken. [121,122] Weitere Reaktionen auf aminoterminierten SAMs werden in den Abschnitten 3.3 und 3.4 diskutiert.…”
Section: Selbstorganisation Funktionalisierter Alkylsilane Und Chemisunclassified
“…Dieses System wurde verwendet, um durch die Absorption von UV-Licht reversible ¾nderungen der Benetzbarkeit durch das Schalten zu einem polareren, zwitterionischen Merocyanin-Isomer zu bewirken. [121,122] Weitere Reaktionen auf aminoterminierten SAMs werden in den Abschnitten 3.3 und 3.4 diskutiert.…”
Section: Selbstorganisation Funktionalisierter Alkylsilane Und Chemisunclassified
“…These stimuli-induced transformations are commonly a result of changes in electrochemical potential, [3] pH, [4] solvent, [5] or irradiation. [6] In previous years, many different and innovative approaches have been explored using these stimuli as tools. Katz et al demonstrated the reversible change of wettability by using an electrochemically driven translocation of cyclophanes on molecular strings.…”
Section: Introductionmentioning
confidence: 99%
“…Interfacial force microscopy ͑IFM͒ was developed fifteen years ago to avoid these mechanical instability problems [9][10][11] and has contributed to molecular scale understanding of various surface phenomena. IFM has been applied to diverse interfacial researches including nanotribology, [12][13][14] interfacial adhesion, 15,16 probing of interfacial water structures, 17,18 and measurements of chemical interactions. 19,20 However, the technique has not been widely used due to low sensitivity and technical complexity of the electrical-sensing method.…”
mentioning
confidence: 99%